Controlled evaporative self-assembly of Fe3O4 nanoparticles assisted by an external magnetic field. Issue 40 (2nd April 2015) - Men, Yonghong; Wang, Wenqin; Xiao, Peng; Gu, Jincui; Sun, Aihua; Huang, Youju; Zhang, Jiawei; Chen, Tao
Abstract : A simple yet robust approach of magnetic field assisted controlled evaporative self-assembly (CESA) is developed to achieve Fe3 O4 nanoparticles (NPs) micro- and nano-patterns in two dimensional (2D) direction. Abstract : High fidelity and regularity structures of nanoscale materials has opened up new opportunities for developing miniaturized devices. A simple yet robust approach of magnetic field assisted controlled evaporative self-assembly (CESA) is developed to achieve Fe3 O4 nanoparticle (NP) micro- and nano-patterns in a two dimensional (2D) direction. In the magnetic field assisted CESA process, the self-assembly morphology can be well controlled by varying extrinsic and intrinsic variables such as temperature, external magnetic field, and concentration of Fe3 O4 NPs. Under the optimized magnetic field rotation frequency and temperature, 2D self-assembly of Fe3 O4 NPs can be well realized. In addition, as photoactive sites, double bonds on the surface of Fe3 O4 NPs allow the growth of polymer brushes by self-initiated photografting and photopolymerization (SIPGP), and the further achievement of free-standing magnetic composite films with well-defined patterns.